The Key to Happiness in a Sufistic Perspective: Between Classical Sufis and Contemporary Sufis - Nur Hadi Ihsan; Amir Reza Kusuma; Nisrina Uswatunnissa; Riza Maulidia (al-Afkar, Journal For Islamic Studies, 2023)
Today, many people's understanding of the meaning of happiness is limited to what can be counted. So that the meaning of happiness according to ordinary people is when people have a lot of money, are healthy, and are successful in the world. While the meaning true happiness is when humans can reach the blessing of Allah SWT. In this study, we will explain the meaning of happiness according to classical and modern Sufism as well as explanations from several commentators. This study aims to find out the meaning and ways of obtaining true happiness in the perspective of classical and modern Sufi. This paper is a library research that uses documentary techniques to collect data sourced from books, journals and, encyclopedias, dictionaries. The collected data were analyzed using descriptive analysis. This research produces the main points, namely: classical and modern Sufis agree that pleasure, wealth, and other life achievements are not a goal, but merely a means to achieve spiritual happiness. The highest happiness is when you can get closer to Allah (ma'rifatullah) and reach His heaven.